German Reunification and the Legacy of GDR Literature and Culture. - Byrnes, Deirdre (German Monitor Ser., 2018)
Since the tumultuous events of 1989/1990, writers, cultural practitioners and academics have responded to, reconstructed and reflected upon the process and enduring impact of German reunification. This bilingual volume provides a nuanced understanding of the literature and culture of the GDR and its legacy today. It explores a broad range of genres, combines perspectives on both lesser-known and more established writers, and juxtaposes academic articles with the personal reflections of those who directly experienced and engaged with the GDR from within or beyond its borders. Whether creative practitioners or academics, contributors consider the broader literary and intellectual contexts and traditions shaping GDR literature and culture in a way that enriches our understanding of reunification and its legacy. Contributors are: Deirdre Byrnes, Anna Chiarloni, Jean E. Conacher, Sabine Egger, Robert Gillett, Frank Thomas Grub, Jochen Hennig, Nick Hodgin, Frank Hörnigk, Therese Hörnigk, Gisela Holfter, Jeannine Jud, Astrid Köhler, Marieke Krajenbrink, Hannes Krauss, Reinhard Kuhnert, Katja Lange-Müller, Corina Löwe, Hugh Ridley, Kathrin Schmidt.